2018
DOI: 10.1159/000491778
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishable Prognostic Signatures of Left- and Right-Sided Colon Cancer: a Study Based on Sequencing Data

Abstract: Key WordsLeft-and right-sided • Colon cancer • Prognosis • TCGA Abstract Background/Aims: Left-and right-sided colon cancers are considered to be two different diseases and have altered outcomes. However, specific molecules to predict the prognosis of left-and right-sided colon cancers are currently lacking. Methods: Expression profiling of colon cancer were downloaded from The Cancer Genome Atlas (TCGA). Differentially expressed genes (DEGs) of left-and right-sided colon cancers were compared by DESeq analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…This latter finding is consistent with results reported by Liang et al demonstrating that left-sided colon cancer in patients with advanced stages exhibit poorer survival than those with right-sided colon cancers. 36 However, we found that the ppCD8sig scores did not differ between males and female (online supplemental figure 4B) or age groups (online supplemental figure 4C). Altogether, TCGA analysis supports that the gene signature identified from our gene expression profiling can predict poorer survival and more aggressive clinicopathological features, and could be reflective of the level or the activity of CD8 + T cells in human CRC.…”
Section: Functional Enrichment Analysis Of Steadily Deregulated Genesmentioning
confidence: 67%
“…This latter finding is consistent with results reported by Liang et al demonstrating that left-sided colon cancer in patients with advanced stages exhibit poorer survival than those with right-sided colon cancers. 36 However, we found that the ppCD8sig scores did not differ between males and female (online supplemental figure 4B) or age groups (online supplemental figure 4C). Altogether, TCGA analysis supports that the gene signature identified from our gene expression profiling can predict poorer survival and more aggressive clinicopathological features, and could be reflective of the level or the activity of CD8 + T cells in human CRC.…”
Section: Functional Enrichment Analysis Of Steadily Deregulated Genesmentioning
confidence: 67%
“…org/package=survivalROC; version 1.0.3), which provides an effective approach for evaluating time-dependent ROC using censored data. To quantitatively evaluate the prognostic value, the area under the curve (AUC) of the ROC curves was calculated (24,(43)(44)(45)(46)(47)(48).…”
Section: Risk Score Constructionmentioning
confidence: 99%
“…Based on tumor location, COAD includes at least two types [3], left colon adenocarcinoma (LCOAD) and right colon adenocarcinoma (RCOAD). LCOAD refers to tumors from the splenic flexure of the colon to the sigmoid colon, and RCOAD refers to tumors between the ileocecal region and the transverse colon [4]. In addition to their different origins, LCOAD and RCOAD also have different clinical manifestations, histological types, molecular characteristics, prognoses, modes of metastasis, and treatment options [3], which are reflected in the following aspects.…”
Section: Introductionmentioning
confidence: 99%